Experimental Investigation of Wave-Induced Ship Hydroelastic Vibrations by Large-Scale Model Measurement in Coastal Waves - Jialong Jiao; Huilong Ren; Shuzheng Sun; Christiaan Adika Adenya (Shock and Vibration)
Ship hydroelastic vibration is an issue involving mutual interactions among inertial, hydrodynamic, and elastic forces. The conventional laboratory tests for wave-induced hydroelastic vibrations of ships are performed in tank conditions. An alternative approach to the conventional laboratory basin measurement, proposed in this paper, is to perform tests by large-scale model measurement in real sea waves. In order to perform this kind of novel experimental measurement, a large-scale free running model and the experiment scheme are proposed and introduced. The proposed testing methodology is quite general and applicable to a wide range of ship hydrodynamic experimental research. The testing procedure is presented by illustrating a 5-hour voyage trial of the large-scale model carried out at Huludao harbor of China in August 2015. Hammer tests were performed to identify the natural frequencies of the ship model at the beginning of the tests. Then a series of tests under different sailing conditions were carried out to investigate the vibrational characteristics of the model. As a postvoyage analysis, load, pressure, acceleration, and motion responses of the model are studied with respect to different time durations based on the measured data.